Multigene Phylogeny and Morphology Reveal Three Novel Species and a Novel Record of Agaricus From Northern Thailand - Jaichaliaw, Chanyawat; Kumla, Jaturong; Vadthanarat, Santhiti; Suwannarach, Nakarin; Lumyong, Saisamorn (Frontiers in Microbiology, 2021)
Agaricus is a saprophytic mushroom genus widely distributed throughout the world. In this study, a survey of the Agaricus species carried out around Chiang Mai University in northern Thailand from 2018 to 2019 yielded twelve collections. Morphological characteristics and phylogenic analyses based on the internal transcribed spacers (ITS) and a fragment of the large subunit (LSU) of the nuclear ribosomal DNA (rDNA), and a fragment of the translation elongation factor 1-alpha (tef1) genes were investigated. The result was revealed that these collections belong to six species including A. erectosquamosus, A. pallidobrunneus, A. subrufescens and three new species. Agaricus thailandensis sp. nov. was found to belong to Agaricus sect. Minores, which is placed in Agaricus subg. Minores. Aagricus pseudoerectosquamosus sp. nov. was placed in Agaricus sect. Brunneopicti within Agaricus subg. Pseudochitonia. Furthermore, A. lannaensis remains an incertae sedis in Agaricus subg. Pseudochitonia. Additionally, it has been proposed that A. pallidobrunneus was discovered in Thailand for the first time. Full descriptions, color photographs, illustrations and phylogenetic trees are provided.